Exposure to outdoor aerospora and associated respiratory health risks among adults in Potchefstroom, North-West province, South Africa - Gharbi, Dorra; Neumann, Frank Harald; Podile, Keneilwe; McDonald, Marinda; Linde, Jo-hanné; Frampton, Megan; Liebenberg, Jennifer Leigh; Cilliers, Sarel; Mmatladi, Tshiamo; Nkosi, Phumelele; Paledi, Keamogestswe; Piketh, Stuart; et al. (Frontiers in Allergy, 2025)
BackgroundData on allergic rhinitis and respiratory health metrics are limited for South Africa, with grass pollen as a key outdoor aeroallergen. Exotic trees such as plane trees and ragweed produce highly allergenic pollen, dominating indigenous trees and weeds. Pollen allergy prevalence data is lacking in cities of North-West province such as Potchefstroom.ObjectivesThis study aimed to (i) assess the prevalence of allergies to major aeroallergens, including Poaceae (grasses), Cupressus/Hesperocyparis (cypresses), Platanus (plane tree), Ulmus (elm), Quercus (oak), Betula (birch), Olea (olive), Artemisia (sagebrush), Amaranthus (amaranth), Plantago (plantain), Morus (mulberry), and Ambrosia (ragweed), along with fungal spores such as Alternaria, Cladosporium, and Penicillium/Aspergillus, and (ii) investigate the monthly incidence of major aeroallergens and reactivity levels in sensitized adults in Potchefstroom.MethodsSkin prick tests (SPTs) were performed on 202 adults aged 18–64 years with confirmed allergic symptoms during a field campaign at North-West University (NWU)'s Potchefstroom campus. A test panel of grass, weed, tree, and fungal spore extracts previously identified via aerobiological monitoring was used. Symptom scores were recorded using ISAAC questionnaires; Spearman's statistical correlation between symptom frequency and monthly aeroallergen concentrations were analyzed.ResultsAmong the participants, 184 (91%) exhibited positive SPT reactions: 104 (57%) are monosensitized to pollen, 45 (24%) to fungal spores, and 35 (19%) are polysensitized. Aeroallergen prevalence was higher in females (73%) than in males (27%). The most common pollen allergens were Cynodon dactylon (Bermuda grass) (85%), Zea mays (maize) (46%), Platanus spp. (plane tree) (35%), and Ulmus campestris (field elm) (33%). Among fungal spores, Alternaria was the most common (93%), followed by Cladosporium (27%). A significant and positive statistical correlation was found between allergic rhinitis symptoms and monthly pollen concentrations of Betula, Morus, Platanus, and Quercus.Discussion & ConclusionThis pilot study linked aeroallergens detected in Potchefstroom with allergy profiles of local residents. The findings highlight the need for more comprehensive regional studies that integrate allergen testing with aerobiological data. Raising awareness and implementing health strategies are essential for managing allergic rhinitis in South Africa. More affordable and available SPTs kits, adapted to allergy prevalence in South Africa, are strongly suggested.